Antibiogram of Nosocomial Infections and Its Antimicrobial Drug Resistance - Saranraj, P. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Nosocomial infections occur worldwide and affect both developed and resource-poor countries. Infections acquired in health care settings are among the major causes of death and increased morbidity among hospitalized patients. Antibiograms are the aggregate percentages of organisms susceptible to various antibiotics on a hospital formulary and are usually presented on an annual basis. The main purpose of this information is to guide empiric antimicrobial therapy before specific patient culture results are available. The prevalence of nosocomial infection causing bacteria and their antimicrobial susceptibility pattern are reviewed in this study. Antibiograms are used to track the antibiotic resistance patterns of clinically important microorganisms detected by laboratories. Hospital antibiograms can be used to provide useful information for the selection of an empiric therapy for a presumptive diagnosis as well as detect trends towards antimicrobial resistance. Hospital laboratories usually generate an antibiogram from every six to twelve months and the data is then entered into an antibiogram database. Limitations of hospital antibiograms are that they do not sort out community-acquired infections from nosocomial infections and some laboratories may not thoroughly unduplicate their data, thus giving a picture of a larger number of resistant isolates than is the case. This review assesses the following topics: Impact of nosocomial infection, Nosocomial infection sites, Microorganisms causing nosocomial infections, Methods of acquisition of nosocomial infections, Antimicrobial use and drug resistance in nosocomial infection, Antibiogram of nosocomial infection causing bacteria and Limitation of antibiogram.